Death and torture: contesting narratives and sites of resistance - Donnelly, Faye (Contesting torture, 2023)
This chapter explores the complex and ambiguous entanglements that exist between torture and death. Surprisingly, as we show, death remains a marginal topic in torture debates. Existing accounts also tend to frame violent power imbalances between torturers and the tortured as insurmountable and fixed. While powerful, these arguments contain blind spots. Throughout this chapter, we engage with debates taking place around death and dead bodies to cast a different light on what torture is and how it works. In part, we detail how the fear of death can be employed as a torture tactic. We also argue that in some instances tortured people have managed to overcome fear, thereby defying their captors and the act of torture. These discussions bridge into our exploration of alternative sites of contestation. Ultimately, we suggest that people who die from torture can be ‘brought back to life’ through processes of civic resistance. We close with some incomplete endings and invitations.